2014
DOI: 10.1002/adma.201403889
|View full text |Cite
|
Sign up to set email alerts
|

A Multitheragnostic Nanobubble System to Induce Blood–Brain Barrier Disruption with Magnetically Guided Focused Ultrasound

Abstract: A novel magnetically guidable nanobubble is designed for disrupting the blood-brain barrier (BBB) by combining magnetic guidance with focused ultrasound in vivo. The magnetic-nanobubble platform also demonstrates the potential to serve as a unique theranostic tool via performing focused ultrasound (FUS)-induced BBB disruption and magnetic resonance imaging (MRI)/ultrasound dual-modality contrast-agent imaging to improve the drug delivery of therapeutic substances or gene therapy into the central nervous system. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 35 publications
2
82
0
2
Order By: Relevance
“…Few reports have been published regarding the synthesis of MMBs, which are stabilized by a polymeric, [13][14][15][16] lipid 17,18 or silica 19 shell, and the incorporation of magnetic and therapeutic NPs. In these published studies, the shells of MMBs are normally intact, which hinders MB oscillation at low-amplitude driving forces.…”
Section: Preparation Of Mmbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few reports have been published regarding the synthesis of MMBs, which are stabilized by a polymeric, [13][14][15][16] lipid 17,18 or silica 19 shell, and the incorporation of magnetic and therapeutic NPs. In these published studies, the shells of MMBs are normally intact, which hinders MB oscillation at low-amplitude driving forces.…”
Section: Preparation Of Mmbsmentioning
confidence: 99%
“…20 As a result, the release of particle cargo relies on the abrupt collapse and accompanying shell disruption of each MB under high-amplitude driving forces of 3-10 bars. 16,18,19 Such rapid and asymmetrical collapse (that is, cavitation) results in high shear flows, microjets and microstreaming 21 that damage surrounding tissues, such as the endothelium. [4][5][6][7] Furthermore, the synchronous burst release of drugs could exceed toxic limits, limiting the clinical application of these MMBs.…”
Section: Preparation Of Mmbsmentioning
confidence: 99%
“…Finally, recent work suggested that sub-micrometer, nanobubbles (as opposed to supramicrometer microbubbles) may have applications for FUS as well. While nanobubbles have lower ultrasound scattering efficiency than microbubbles, they can penetrate disrupted tumor vascular beds, can be more stable than microbubbles, and are also less likely to undergo inertial cavitation and cause micro hemorrhages [28,29,30,31,32]. A study by Huang et al [28] demonstrated that magnetically guidable nanobubbles can disrupt the BBB and serve as a contrast-enhancing agent for ultrasound (US) and MRI, while causing a lower rate of erythrocyte extravasation than their supra-micrometer sizes counterparts or a commercially available, lipid-based microbubble [28].…”
Section: Strategies For Cns Deliverymentioning
confidence: 99%
“…Huang et al recently fabricated a multi-theranostic nanobubble system by synthesizing nanobubbles using mesoporous silica SPION shell nanoparticles loaded with perfluoropentane. They act as Magnetic resonance imaging (MRI)/US dual-modality contrast agent and cause FUS-induced BBB disruption [184]. This multimodal nanoparticle imaging system has the potential to be used along with gene carriers to deliver therapeutic genes across the BBB for the treatment of glioma cancer.…”
Section: Challenges Associated With and Future Directions Of Triggmentioning
confidence: 99%